2019
DOI: 10.1063/1.5091798
|View full text |Cite
|
Sign up to set email alerts
|

X-ray sources using a picosecond laser driven plasma accelerator

Abstract: X-ray photon beams in the keV to MeV energy range are essential to study high energy density (HED) matter and to improve the understanding of inertial confinement fusion and astrophysical systems. HED experiments produce highly transient matter under extreme states of temperatures and pressures and it is essential to develop light sources that are: in the hard x-ray energy range (0.01-1 MeV), directional, high-yield, low-divergence, and short-duration (ps and sub-ps). In this work we show that by using a laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
0
19
1
1
Order By: Relevance
“…This divergence demonstrates a major step forward in the possible quality of electron beams from SMLWFA since it is significantly reduced from the next best divergence reported from other SMLWFA experiments (64 × 100 mrad ± 10 mrad 6 ) and is on the order of the divergences (< 10 mrad) of the electron beams produced by LWFA being driven by ultrashort-pulse lasers (τ < λ p ). The possibility of lower-divergence electron beams from SMLWFA-based LPAs increases their utility when using the produced electron beams to generate compact sources of high-energy electrons for conversion to photons and positrons.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…This divergence demonstrates a major step forward in the possible quality of electron beams from SMLWFA since it is significantly reduced from the next best divergence reported from other SMLWFA experiments (64 × 100 mrad ± 10 mrad 6 ) and is on the order of the divergences (< 10 mrad) of the electron beams produced by LWFA being driven by ultrashort-pulse lasers (τ < λ p ). The possibility of lower-divergence electron beams from SMLWFA-based LPAs increases their utility when using the produced electron beams to generate compact sources of high-energy electrons for conversion to photons and positrons.…”
Section: Resultsmentioning
confidence: 67%
“…For the lowest-divergence electron beam reported here, that source size would be approximately half of that produced by the electron beam from Ref. 6 . Lower-divergence electron beams also reduce the background noise in these applications.…”
Section: Resultsmentioning
confidence: 88%
“…At densities around 10 18 cm −3 the acceleration gradient in these accelerators is thus several orders of magnitude higher than the breakdown fields in conventional radio-frequency (RF) accelerators (∼ 100 MV m −1 ), al-lowing for a significant downsizing of the accelerator. LWFA experiments are routinely performed at numerous high-power laser facilities [3][4][5][6][7][8][9][10][11] and reach high charge (∼ nC) [12,13] combined with an ultra-short bunch duration (∼ 10 fs) [14,15], resulting in high peak currents of tens of kA [13,16]. Furthermore, the bunches typically have a few-micrometer source size at the exit of the accelerator [17][18][19], which is paired with few-mrad divergence [12,20].…”
Section: Introductionmentioning
confidence: 99%
“…In underdense plasma, hydrodynamic expansion of an optical field-ionized plasma column forms a low-density channel which has been proposed [ 1 ] and demonstrated [ 2 ] as a method of guiding high-power driving pulses to obviate the need for capillary guiding structures in high-energy laser Wakefield accelerators. Further, Lemos et al [ 3 ] demonstrated production of betatron radiation and inverse Compton scattering from the interaction of picosecond-scale laser pulses with a supersonic gas jet (and in the latter case, a plasma mirror). Future applications of this work will be heavily reliant on the reliable direction of the outgoing radiation.…”
Section: Introductionmentioning
confidence: 99%